Forward Head Posture (FHP) Condition: Reliability of Craniovertebral Angle (CVA) Testing - Ika Guslanda Bustam; Dwi Herdayanti (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
Background: Forward Head Posture (FHP) is a prevalent postural misalignment associated with various musculoskeletal and functional disorders. Accurate assessment of FHP is crucial for effective diagnosis and treatment. The Craniovertebral Angle (CVA) test is commonly utilized to quantify the degree of FHP, but its reliability remains a topic of interest. Objective: This study aims to evaluate the reliability of CVA testing in assessing FHP by analyzing intra-rater and inter-rater consistency in clinical settings. Methods: Studies were selected based on specific inclusion criteria, including those with defined methods for measuring CVA and reporting on reliability statistics. Data were extracted and synthesized to determine the overall reliability of CVA testing. Results: The analysis revealed that CVA testing demonstrates high intra-rater reliability with intraclass correlation coefficients (ICCs) 0.98. Inter-rater reliability also showed strong consistency, with ICCs 0.95. Variability in reliability was observed based on methodological differences, including measurement techniques and rater experience. Conclusion: CVA testing is a reliable method for assessing Forward Head Posture, with high intra-rater and inter-rater consistency. This reliability supports the use of CVA measurements by using clinometer for evaluating FHP. However, standardization of measurement protocols and rater training are recommended to further enhance reliability and accuracy.